Legal reform and the erosion of deterrence: Reassessing remission and conditional release policies for corruption convicts - Desita, Annisthasya; Ridwan (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Granting remission and parole to prisoners is the authority held by the Correctional Institution, in accordance with the provisions contained in Law Number 22 of 2022 concerning Corrections. The main requirement for obtaining remission and parole is the good behavior of the prisoner, and this provision applies to all prisoners without exception, including prisoners involved in criminal acts of corruption. Methods: This study uses the Normative Juridical method with a descriptive analysis approach. The research data was obtained through two sources, namely primary data from Legislation and secondary data obtained from interviews with Class IIA Tangerang Prison Officers. Findings: The results of the study show that the revocation of the Government Regulation has eliminated strict requirements related to granting remission to prisoners involved in corruption crimes, making it easy for corrupt prisoners to obtain it, it has eliminated the deterrent effect for perpetrators and the community. In response to this situation, total reform is needed, namely legal reform, law enforcement officers, and culture. Conclusion: The study concludes that the revocation of strict regulations has made it easier for corruption convicts to obtain remission, weakening the deterrent effect. Therefore, comprehensive reforms in law, enforcement, and legal culture are urgently needed. Novelty/Originality of this article: This article offers a critical and original analysis of the impact of regulatory changes on the remission process for corruption convicts in Indonesia. By combining normative legal review with firsthand insights from correctional officers, it highlights the unintended consequences of deregulation—specifically the erosion of deterrent effects—and emphasizes the urgent need for systemic legal reform, a perspective that has been underexplored in prior studies.